Analisa Ukuran Partikel Serbuk Komposit NiCrAl dengan Penambahan Reaktif Elemen untuk Aplikasi Lapisan Tahan Panas [Particle Size Analysis of NiCrAl Composite Powders with Reactive Elements Addition for Thermal Barrier Coating Applications] - Desiati, Resetiana Dwi; Sugiarti, Eni; Ramandhany, Safitry (Jurnal Metalurgi, 2018)
In this paper we discuss about the particle size of NiCrAl powder in addition to reactive elements, i.e. yttrium (Y), silicon (Si), hafnium (Hf), and zirconium (Zr) to produce compound powder of NiCrAlY, NiCrAlSi, NiCrAlYSi, NiCrAlHf, and NiCrAlZr produced by milling process using ball mill for 36 hours at rotating speed of 25 Hz or 1500 rpm and the ball to powder ratio (BPR) of 1:2. Scanning electron microscopy (SEM) was used to characterize the powder sample to understand the morphology of the sample such as particle shape and size. Digital picture of SEM results was analyzed using free software ImageJ to understand the particle size and the results was compared by using characterization results of Particle Size Analizer (PSA). Analysis of NiCrAl powder on at 0 hour (before milling) has a value of 44.04 μm based on PSA data, while based on ImageJ processing data NiCrAl powder has an average value of 46.98 μm. On the contrary, the PSA data on the classification of NiCrAl powder after 36 hours of milling time has a particle size of 71.12 μm whereas ImageJ processing data has an average value of 67.93 μm. These analysis methods have also been applied to NiCrAlSi, NiCrAlYSi, NiCrAlHf, and NiCrAlZr powders. Therefore, analysis results reveal that the digital processing of SEM image using ImageJ has an accuracy value of abaut 80% compared with PSA data. It is caused by the shape of powder sample which was not homogenous and not well-distributed. In addition, the SEM results show that the particle size of compound powder of NiCrAl, NiCrAlY, NiCrAlSi, NiCrAlYSi, NiCrAlHf, and NiCrAlZr after 36 hours was larger than the initial condition or 0 hours of milling time due to agglomeration and cold welding during milling process. The addition of reactive elements with small compositions to NiCrAl has no impact on particle size.